Phenolic profiling of Veronica spp. grown in mountain, urban and sand soil environments - Barreira, João C.M. (2014)
Veronica (Plantaginaceae) genus is widely distributed in different habitats. Phytochemistry studies are increasing because most metabolites with pharmacological interest are obtained from plants. The phenolic compounds of V. montana, V. polita and V. spuria were tentatively identified by HPLC-DAD-ESI/MS. The phenolic profiles showed that flavones were the major compounds (V. montana: 7 phenolic acids, 5 flavones, 4 phenylethanoids and 1 isoflavone; V. polita: 10 flavones, 5 phenolic acids, 2 phenylethanoids, 1 flavonol and 1 isoflavone; V. spuria: 10 phenolic acids, 5 flavones, 2 flavonols, 2 phenylethanoids and 1 isoflavone), despite the overall predominance of flavones. V. spuria presented the highest contents in all groups of phenolic compounds, except flavones, which did not show differences among the assayed species. The detected differences proved to be significant, as confirmed by objects distribution obtained in PCA. Overall, these species might be considered good sources of phenolic compounds for industrial or pharmacological applications.